Trigger-Free and Low-Cross-Sensitivity Displacement Sensing System Using a Wavelength-Swept Laser and a Cascaded Balloon-like Interferometer - Jianming Zhou; Jinying Fan; Junkai Zhang; Jianping Yao; Jiejun Zhang (Sensors)
A wavelength-swept laser (WSL) demodulation system offers a unique time-domain analysis solution for high-sensitivity optical fiber sensors, providing a high-resolution and high-speed method compared to optical spectrum analysis. However, most traditional WSL-demodulated sensing systems require a synchronous trigger signal or an additional optical dispersion link for sensing analysis and typically use a fiber Bragg grating (FBG) as the sensing unit, which limits displacement sensitivity and increases fabrication costs. We present a novel displacement sensing system that combines a trigger-free WSL demodulation method with a cascaded balloon-like interferometer, featuring a simple structure, high sensitivity, and low temperature cross-sensitivity. The sensor is implemented by bending a short length of single-mode fiber with an optimal radius of around 4 mm to excite cladding modes, which form an interference spectral response with the core mode. Experimental findings reveal that the system achieves a high sensitivity of 397.6 pm/μm for displacement variation, corresponding to 19.88 ms/μm when demodulated using a WSL with a sweeping speed of 20 nm/s. At the same time, the temperature cross-sensitivity is as low as 5 pm/°C or 0.25 ms/°C, making it a strong candidate for displacement sensing in harsh environments with significant temperature interference.